Research on the growth of China's EV market and influencing factors of consumer behaviour - ZHAO, DONGXU (2022)
Electric vehicles with low energy consumption and that are environmentally friendly have become one of the automobile industry's development hotspots, as well as the primary research objects of automobile companies in many countries. It corresponds to people's desire for a greener lifestyle and aids in the realization of the beautiful vision of sustainable development. To encourage the quick expansion of the electric car sector, the Chinese government has implemented a number of preferential regulations. This study constructs a framework of factors affecting the purchase behaviour of electric vehicles from three aspects of demographics, situation, and psychology, and discusses the consumer behaviour of Chinese consumers for electric vehicles, based on planned behaviour theory, innovation diffusion theory, and existing research results. Demographics, technical attributes, cost, brand, government policy, environmental consciousness, subjective norms, and product knowledge and experience were all found to be predictors of consumers' purchase behaviour of electric vehicles in this study. The primary data was acquired using an online questionnaire, and multiple regression analysis was used to assess the relevant factors. The findings reveal that product knowledge and experience, technical characteristics, and government policies all have a significant positive impact on electric vehicle consumer behaviour, while cost has a significant negative impact on electric vehicle consumer behaviour.